Protocatechuic acid ameliorates neurobehavioral defìcits via suppression of H) oxidative damage, inflammation, caspase-3 and acetylcholinesterase activities in diabetic rats (2019)
Clinical and experimental data have demonstrated that diabetes is associated with neurological complications. Protocatechuic acid (PCA) is a phenolic phytochemical widely reported to possess antidiabetic property. However, there is no scientific information on the influence of PCA on diabetes-induced neurotoxicity. The present study aimed at investigating the neuroprotective mechanism of PCA in streptozotozin (STZ)-induced type 1 diabetic rats orally treated with PCA (50 mg/kg body weight) or glibenclamide (5 mg/kg body weight) for 45 consecutive days. Locomotor behavior was analyzed using video-tracking software during the 8-min trial in a novel environment whereas the pancreas, cerebrum and cerebellum of the rats were processed for biochemical analyses. Results showed that treatment of diabetic rats with PCA at 50 mg/kg significantly (p < 0.05) im- proved the locomotor and motor activities including the average speed, total time mobile, distance travelled, body rotation, turn angle, forelimb grip and grooming when compared with untreated diabetic rats. Moreover, the prevention of diabetes-mediated increase in acetylcholinesterase activity, biomarkers of inflammatory and oxidative stress as well as caspase 3 activity by PCA treatment was accompanied by improved pancreatic, cer- ebral and cerebellar architectures. Collectively, the neuroprotective mechanisms of PCA is related to its anti- oxidant, anti-inflammatory and anti-apoptotic activities.